Study on the Characteristics of Self-Stabilizing Height Distribution for Deep Foundation Pit Vertical Sidewall in Binary Strata of Upper Soil and Lower Rock - Zhang Ziguang; Yihang Li; Jiesheng Zhang; Tao Xu; Guangyong Cao; YiKang Xu (Advances in Civil Engineering)
The self-stability height of the foundation pit sidewall is an important criterion for evaluating the safety degree and designing the supporting structure. The strength reduction elastic-plastic finite element numerical calculation method has been adopted in this paper. Based on comparative analysis of the stability characteristics for deep foundation pit in binary strata of upper soil and lower rock under multiple working conditions, the potential fracture surface of deep foundation pit and the evolution law of corresponding safety factor have been revealed under different Hs and H. A new idea that the vertical soil sidewall height (Hs) and the vertical rock sidewall height (Hr) are used as two independent evaluation indexes, respectively, for deep foundation pit stability in binary strata of upper soil and lower rock has been put forward. The distribution characteristics and variation law of Hs0 and Hr0 under different Hs and different H have been revealed, respectively. The spatial distribution map of the self-stabilizing height for deep foundation pit vertical sidewall in upper soil and lower rock binary stratum has been constructed, and the mathematical fitting equation between Hr0 and Hs has been obtained. Finally, combined with the implementation effect of the deep foundation pit project of Ningxia Road Station for Qingdao Metro Line 3, the rationality of the conclusions is verified. The research results provide theoretical basis for quickly determining the self-stability characteristics of foundation pit vertical sidewall.